PENGARUH METODE DETERMINASI TERHADAP NILAI ENERGI METABOLIS DEDAK PADI - Zakaria, Achmanu (BUANA SAINS, 2006)
Three experiments were done to study the apparent and true metabolizable energy (AMEN and TME) values of rice bran determined with broiler chicken and duck. In experiment I, 48 broiler of 6 weeks old consisting male and female broiler were divided into 8 group, 3 birds each. Each group was fed experimental feed i.e. basal, mix of basal and rice bran (50:50) and pure rice bran according to determination methods which were Farrell, Terpstra (Spelderholt Quantitative Method) and Sibbald method. Experiment II used 10 male broiler chickens of 6 week old and 1250 ± 9,6 g body weight and 10 male ducks of 8 week old and 1300 ± 11,2 g body weight. Five of them were unfed for correcting the endogenous excreta energy. The results of experiment I indicated that the metabolizable energy values of rice bran determined on three methods was significantly different. The TME values of rice bran was higher than AMEn values which determined with Farrell method and Terpstra method and the values higher if determined with Farrell method than Terpstra method. The results of experiment II indicated that the AMEn value of rice bran which determined with duck was higher then chicken but the TME values was not significantly different. The result of experiment III indicated that the TME values of rice bran were influenced by the quality. Each quality of rice bran had higher TME values if determination, species, sex and quality of the rice bran